Age, growth and yield-per-recruit analysis of ndunduma Diplotaxodon limnothrissa (Teleostei: Cichlidae), in the southeastern arm of Lake Malawi - Kanyerere, Geoffrey Zantute (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2004)
Diplotaxodon limnothrissa Turner (1995) is a widely distributed species occurring throughout Lake Malawi, extending from the surface to a depth of at least 220m. It is probably the most abundant cichlid in the lake with biomass estimates of around 87 000 tonnes in the pelagic zone alone. The species is exploited commercially in the southern part of the lake but since its inception the fishery has never been assessed. As such this study investigates some aspects of age and growth of the species besides applying a yield-per-recruit analysis to assess the status of the fishery. Analysis of sectioned sagittal otoliths revealed that D. limnothrissa is fast growing and relatively long-lived species, attaining ages in excess of 10 years. Growth in length was rapid in immature fish, with fish attaining almost half of their maximum size within their first year. Le ngth-at-age was described by the von Bertalanffy growth model with combined-sex growth described as Lt = 211.21(1-exp(- 0.24(t+1.36))) mm TL. Total, natural and fishing mortalities were estimated at 0.76 yrâ »Â¹, 0.31 yrâ »Â¹ and 0.45 yrâ »Â¹ respectively. Per-recruit analysis indicated that the D. limnothrissa stock in the southeast arm of the lake is fully exploited as indicated by the current spawner biomass-per-recruit ratios of 31-55% (SB/R)F=0. Modelling indicated that the current age-at-capture (2.67 years) is lower than the age at which yield is optimised (> 5 years) based on the Fâ‚€Â·â‚ harvesting strategy. It is, therefore, recommended that the age-at-capture should be increased from 2.67 to 5 years to optimise yield.
Keywords: Fishes -- Nyasa, Lake; Cichlids -- Nyasa, Lake; Fishes -- Growth -- Nyasa, Lake; Fishes -- Age -- Nyasa, Lake; Fishery resources -- Malawi; Fishery management -- Malawi